If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(9 + u) + -2u = -10 (9 * -9 + u * -9) + -2u = -10 (-81 + -9u) + -2u = -10 Combine like terms: -9u + -2u = -11u -81 + -11u = -10 Solving -81 + -11u = -10 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '81' to each side of the equation. -81 + 81 + -11u = -10 + 81 Combine like terms: -81 + 81 = 0 0 + -11u = -10 + 81 -11u = -10 + 81 Combine like terms: -10 + 81 = 71 -11u = 71 Divide each side by '-11'. u = -6.454545455 Simplifying u = -6.454545455
| 3t+4+t=6 | | (3t^4)(-2t)(5t^6)=x | | -9(9+u)-2u=-10 | | -3+6x=5x-13 | | 6/7*7/8 | | 6/7*7/8 | | 5x+10y=-20findx | | x=56-3x | | 3t+4+t=6 | | 25-2x=-(-6+7) | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | x=56-3x | | 6w-5= | | 0.4x=2.40 | | 2(4y-4)-6=17+y | | 3t+4+t=6 | | 2(4y-4)-6=17+y | | 6w-5= | | 25-2x=-(-6+7) | | 25-2x=-(-6+7) | | 6w-5= | | -2/3[24t-27]=-8[-t-4]-6 | | M/5/6=24 | | 9asd+10=21asd | | 3(k-8)-1(k+5)=23 | | 9asd+10=21asd | | 8m-15=77-3m |